Analisis Kontrastif Modalitas Souda dalam Bahasa Jepang dengan Modalitas Keteramalan dalam Bahasa Indonesia - Rini, S.S.,M.Hum., Elizabeth Ika Hesti Aprilia Nindia; Junitasari, Elyka (Vocational College of Diponegoro University, 2024)
This paper studies the comparison between souda modality in Japanese and predictability modality in Indonesian. This paper also aims to analyze the structure, meaning, as well as the similarities and differences between the Japanese language modality and the Indonesian language modality. The data used in this research came from websites, news sites, novels and short stories. The research method used in this studies is descriptive qualitative. The results of this research indicate that the souda modality can be constructed with verbs and adjectives, and has an approximate meaning based on the sense of sight, information held, and excessive estimates; whereas the predictability modality can be constructed with verbs, adjectives, adverbs, verbal clauses, adjectival clauses, and nominal clauses, and have approximate meanings based on objective and subjective assessments. Based on the analysis, it can be concluded that souda modality in Japanese and predictability modality in Indonesian: markers of predictability 'duga', 'kira', 'rasa’, 'pikir', 'tampaknya', 'kelihatannya', 'sepertinya', 'rasanya' have the same meaning, namely to express estimates, conjectures or suspicions about something, while the difference is that the -souda modality marker is directly constructed with the word it is attached to, while the predictability modality marker can be inserted with another word.